Postharvest UV-B Irradiation Stimulated Ginsenoside Rg1 Biosynthesis through Nitric Oxide (NO) and Jasmonic Acid (JA) in Panax quinquefolius Roots - Zhou, Jie; Ran, Zhi-fang; Yang, Xiao-tong; Li, Jia (Molecules (Basel, Switzerland), 2019)
The study highlights the influence and signal transduction mechanism of postharvest UV-B on the production of Rg1 in Panax quinquefolius roots during the drying process. The results showed that postharvest UV-B irradiation induced generation of nitric oxide (NO), jasmonic acid (JA), and ginsenoside Rg1 of P. quinquefolius roots. The UV-B-induced increase of Rg1 was suppressed by NO-specific scavenger (cPTIO) and NOS inhibitors (PBITU), JA synthesis inhibitor (SHAM), and JA synthesis inhibitor (PrGall), indicating that NO and JA played essential parts in UV-B-induced Rg1. External NO inhibitors treatment inhibited UV-B-induced accumulation of NO and JA, which suggested that NO was located upstream of the JA signal pathway. NO-caused Rg1 was inhibited by SHAM and PrGall, implying JA participated in transmitting signal NO to Rg1 accumulation. In other words, NO mediated the postharvest UV-B-induced Rg1 accumulation by the JA-dependent pathway in P. quinquefolius roots during the drying process, which helps us understand the underlying mechanisms involved in UV-B-induced Rg1 production and provides information helpful for P. quinquefolius production.